2009
DOI: 10.1103/physrevlett.103.193602
|View full text |Cite
|
Sign up to set email alerts
|

Chirped Biphotons and their Compression in Optical Fibers

Abstract: We show that broadband biphoton wavepackets produced via Spontaneous Parametric DownConversion (SPDC) in crystals with linearly aperiodic poling can be easily compressed in time using the effect of group-velocity dispersion in optical fibres. This result could foster important developments in quantum metrology and lithography.PACS numbers: 42.50. Dv, 03.67.Hk, 42.62.Eh One of the central problems in quantum optics is generation of nonclassical light with given spectral and spatiotemporal properties. In part… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 18 publications
3
41
0
Order By: Relevance
“…No frequency expansion of the wavevector is involved, in contrast to Ref. [15] where the analysis was performed analytically and only up to second-order terms in frequency. Fig.…”
Section: Temporal Biphoton Compressionmentioning
confidence: 99%
See 4 more Smart Citations
“…No frequency expansion of the wavevector is involved, in contrast to Ref. [15] where the analysis was performed analytically and only up to second-order terms in frequency. Fig.…”
Section: Temporal Biphoton Compressionmentioning
confidence: 99%
“…[15] it was shown that, in some specific cases, this can be achieved by passing one of the two photon through a normal-dispersion medium, for example a standard optical fiber. This result opens a perspective of a real implementation of the method suggested in Ref.…”
Section: Temporal Biphoton Compressionmentioning
confidence: 99%
See 3 more Smart Citations